Evaluation of Protective Mask Notifications to the Safety Gate/RAPEX System during the COVID-19 Pandemic - Joanna Wierzowiecka; Victoria Dąbrowska (Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie)
Objective: This study aims to assess the protective mask notifications used in the Safety Gate / RAPEX system (an early warning system for managing safety used by the European Commission) between 2020 and 2022 in the context of the COVID-19 pandemic. This study continues research into the impact of the COVID-19 pandemic on the notification of protective masks for this system.